(untitled) (Research, Society and Development, 2022)
This article aims to construct a general view of breast milk donation and breastfeeding in Brazilian`s Milk Banks. In order to do that we reviewed the current scientific literature about this topic. The articles were searched in databases, such as SciELO, LILACS, Google Acadêmico e PubMed. After reading and analyzing the literature, 13 articles were selected to become a part of this literature review. In the discussion, the most critical variables that impact breast milk donation and breastfeeding were listed, independent of their negative or positive value. Among them, we can highlight the donor`s clarification about the donation process, the educational level of the donor, and the socioeconomic background of the donor. In conclusion, the lack of human resources and training of healthcare professionals working in the milk banks represents a great difficulty for the donation process and the expansion of the Brazilian human breast milk network, since there is, to this day, a lack of knowledge about the breastfeeding and donation processes which lowers the number of women willing to donate their breastmilk.